2013
DOI: 10.1002/2013wr013959
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ensemble filtering algorithms and null-space Monte Carlo for parameter estimation and uncertainty quantification using CO2sequestration data

Abstract: [1] Geological storage of CO 2 requires multiphase flow models coupled with key hydrogeologic features to accurately predict the long-term consequences. The prediction uncertainty during geological CO 2 storage requires a computationally efficient and practically useful framework. This paper presents a comparative study between ensemblebased filtering algorithms (En-As) and calibration-constrained null-space Monte Carlo (NSMC) methods. For the En-As, we use the ensemble Kalman filter (EnKF), ensemble smoother … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 83 publications
1
17
1
Order By: Relevance
“…However, the estimate is suboptimal when the forward model contains nonlinearities. After evaluating several possible approaches, Emerick and Reynolds () and Tavakoli et al () concluded that the best approach for nonlinear systems where all data can be used simultaneously is to use the ES‐MDA. In ES‐MDA, an ensemble smoother is applied multiple times.…”
Section: Methodsmentioning
confidence: 99%
“…However, the estimate is suboptimal when the forward model contains nonlinearities. After evaluating several possible approaches, Emerick and Reynolds () and Tavakoli et al () concluded that the best approach for nonlinear systems where all data can be used simultaneously is to use the ES‐MDA. In ES‐MDA, an ensemble smoother is applied multiple times.…”
Section: Methodsmentioning
confidence: 99%
“…We solve the aforementioned auxiliary problems Eqns. (25) for the non-overlapping subdomains Y m as shown in Figure 1. The effective properties at the coarse scale namely: capillary pressure P eff c , porosity φ , and mobility tensor Λ eff α , are computed only once as a pre-processor step prior to the numerical simulation.…”
Section: Local Numerical Homogenizationmentioning
confidence: 99%
“…EnKF is an example of a filter, but we did not use EnKF because all data were available at all times. Emerick and Reynolds (2013) and Tavakoli et al (2013) state that the best approach for nonlinear systems such as ours is to use an Ensemble Smoother with Multiple Data Assimilation (ES-MDA). In ES-MDA, the ensemble smoother is applied iteratively multiple times.…”
Section: Inverse Modelmentioning
confidence: 99%